Pengaruh Loan to Deposit Ratio, Net Interest Margin, Cadangan Kerugian Penurunan Nilai terhadap Non Performing Loan - Martiana, Tina Nurul; Hadi, Yulianto; Sukmawati, Mega; Laela, Ela (The Double Entry Journal, 2022)
The study aimed to exaime the effect of Loan to Deposit Ratio (LDR), Net Interest Margin (NIM) dan Allowance for impairment losses (CKPN) on Non Performing Loan (NPL). The population on this study are bank lised on the stock exchange (BEI) Period 2012–2016. . According to the population characteristic, sample usd in this research amoun 12. This research usd quantitative aproach by usd secondary data of obtained from Otoritas Jasa Keuangan (OJK) website. The value of each variable In this research analyzed by multiple linear regression analysis metod by usd IBM SPSS statistics 21 computer program. From the results of research hypotheses testing not that Loan to Deposit Ratio (LDR) had significant positive effect on Non Performing Loan (NPL), Net Interest Margin (NIM) had no significant negative effect on Non Performing Loan (NPL) and Allowance for impairment losses (CKPN) had significant positive effect on NPL.